New tools for advisory services in less favoured areas: Negotiations towards sustainable systems - Koutsouris A. (Production systems and product quality in sheep and goats, 2001)
Based on approaches relating to 'farming systems', 'social learning' and 'agency' the paper intends to examine the processes of negotiations as tools necessary for the sustainability of goat and sheep farming in LFAs. This is so, since what has to be managed includes people and projects: a wide range of people holding different points of view and issues which are likely to be controversial. The experience of the Development Agency of Karditsa, working with sheep and goat farmers in the Greek mountains, is therefore outlined in order to determine the new roles of extension agents. The article concludes with brief recommendations relating to extension training.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)